Drivers of Private Equity Investment Activity: Are buyout and venture investors really so different? - Roger Kelly (European Investment Fund (EIF), 2010)
This paper investigates the drivers of private equity activity by undertaking a panel data study for 17 European countries. Activity is affected by both cyclical and structural factors. We control for the cyclical factors and examine structural drivers of investment in private equity. We examine whether these drivers are different for venture capital and buyout investors, and find that indeed there is a strong distinction between the factors influencing investment in these two groups of investors. Based on our results, we consider policy options for governments to attract more investment.
Keywords: 330